Optimal Dose of Serotonin Reuptake Inhibitors for Obsessive-Compulsive Disorder in Adults: A Systematic Review and Dose–Response Meta-Analysis - Xu, Jiao; Hao, Qinjian; Qian, Ruiyi; Mu, Xingyu; Dai, Minhan; Wu, Yulu; Tang, Yiguo; Xie, Min; Wang, Qiang (Frontiers in Psychiatry, 2021)
Background: Obsessive-compulsive disorder (OCD) is a common chronic mental disorder with a high disability rate. Serotonin reuptake inhibitors (SRIs), including selective serotonin reuptake inhibitors (SSRIs) and tricyclic antidepressants, such as clomipramine, are the most common choices for the pharmacological treatment of OCD. Optimizing their use is pivotal in guiding clinical practice of OCD. However, there are few studies on the optimal dose of SRIs and there is controversy about their dose–response relationship and optimal target dose. Therefore, the objective of this study was to summarize the relationship between the dose and effect of SRIs, as well as the optimal dose of SRIs for OCD, as to propose future research directions. Methods: Medline, Embase, Biosis, PsycINFO, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, and CINAHL were searched for relevant publications, and the search was up to February 22, 2020. We used a one-stage, robust error meta-regression (REMR) model to deal with the correlated dose–response data for SRIs from different studies. Doses of SRIs were converted to fluoxetine equivalents when performing dose–response analysis. Review Manager Program Version 5.3 and STATA software package (version 15.1) were applied to analyze data. The study protocol was registered with PROSPERO (number CRD42020168344). Results: Eleven studies involving 2,322 participants were included in final analysis. For SRIs, the dose–efficacy curve showed a gradual increase trend in the 0–40-mg dose range and then had a decreased trend in doses up to 100 mg fluoxetine equivalent. Dropouts due to adverse effects gradually increased throughout the inspected dose slope. The curve of dose of all-cause dropouts suggested no relationship between them. Sensitivity analysis proved that these results were robust. Conclusion: The systematic review found that the optimal dose for efficacy was about 40mg fluoxetine equivalent. Tolerability decreased with increased doses, and there was no significant correlation between acceptability and doses of SRIs. Therefore, the optimal dose of SRIs needs to consider effectiveness and tolerability. Systematic Review Registration: [PROSPERO], identifier [CRD42020168344].